2011
DOI: 10.1007/s10164-011-0289-6
|View full text |Cite
|
Sign up to set email alerts
|

Female preference in the context of male–male interactions in Maylandia zebra of Lake Malawi

Abstract: The mbuna cichlids of Lake Malawi are a diverse, monophyletic, and recently derived clade. Sexual selection is thought to have accelerated their rapid diversification, though the mechanism by which this has occurred remains unknown. In this study, we examine the effect that male-male interactions have on female preference. We first used a short interaction experiment as a proxy for male dominance. We then measured female preference for (1) a single, isolated male; (2) a group of three, highly ranked males, rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…If M. zebra males use spectral information and/ or sound amplitude to assess an opponent's size, they are expected to escalate fights less with an opponent producing lower frequency and/or louder sounds characteristic of larger fish in comparison with males perceived as smaller. Note that agonistic interactions occurred often between males of different sizes in stock tanks in our facilities, so aggression is expected to occur even when there are perceived asymmetries in the opponent's size, with differences in body size determining aggression level and fight outcome (Mellor et al, 2012). In addition, as fish were matched in size, but the delivered acoustic signals provided mismatched sizeinformation, the experiments aimed to test the prevalence of the acoustic versus the visual sensory channels in fish fights.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…If M. zebra males use spectral information and/ or sound amplitude to assess an opponent's size, they are expected to escalate fights less with an opponent producing lower frequency and/or louder sounds characteristic of larger fish in comparison with males perceived as smaller. Note that agonistic interactions occurred often between males of different sizes in stock tanks in our facilities, so aggression is expected to occur even when there are perceived asymmetries in the opponent's size, with differences in body size determining aggression level and fight outcome (Mellor et al, 2012). In addition, as fish were matched in size, but the delivered acoustic signals provided mismatched sizeinformation, the experiments aimed to test the prevalence of the acoustic versus the visual sensory channels in fish fights.…”
Section: Experimental Designmentioning
confidence: 99%
“…The African cichlid Metriaclima zebra (Boulenger 1899) is a vocal territorial fish for which body size is a critical determinant of fight outcome (Simões et al, 2008;Mellor et al, 2012). Males of this species use visual and acoustic cues (Simões et al, 2008;Bertucci et al, 2012), and likely chemical and vibrational (lateral line) cues, in male-male fighting ability assessment and in a reproductive context (Butler and Maruska, 2015;Escobar-Camacho and Carleton, 2015;Keller-Costa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several communication channels are known to be widely used by fish. Many authors have proposed that visual ( Rosenthal & Ryan, 2000 ; Dijkstra et al, 2010 ; Chen & Fernald, 2011 ; Mellor et al, 2012 ), acoustic ( Amorim et al, 2008 ; Bertucci et al, 2010 ; Maruska, Ung & Fernald, 2012 ; Longrie et al, 2013 ) and chemical cues ( Plenderleith et al, 2005 ; Martinovic-Weigelt et al, 2012 ; Keller-Costa, Canário & Hubbard, 2015 ) are highly relevant for intraspecific communication. Additional studies revealed the importance of the lateral line system during social encounters ( Butler & Maruska, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several communication channels are known to be widely used by fish. Many authors have proposed that visual (Rosenthal & Ryan, 2000;Dijkstra et al, 2010;Chen & Fernald, 2011;Mellor et al, 2012), acoustic (Amorim et al, 2008;Bertucci et al, 2010;Maruska, Ung & Fernald, 2012;Longrie et al, 2013) and chemical cues (Plenderleith et al, 2005;Martinovic-Weigelt et al, 2012;Keller-Costa, Canário & Hubbard, 2015) are highly relevant for intraspecific communication. Additional studies revealed the importance of the lateral line system during social encounters (Butler & Maruska, 2015).…”
Section: Introductionmentioning
confidence: 99%